2020
DOI: 10.3390/coatings10020109
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite-Synergized Water-Based Intumescent Flame Retardant Coating for Plywood

Abstract: In this study, montmorillonite (MMT) was used as an inorganic synergist to prepare the water-based intumescent flame retardant (IFR) ornamental coating for plywood. Results indicate that the 7 wt.% MMT modified IFR coating (No. 3) possess the best fire resistance (longer than 20 min) of the tested samples according to the fire performance, which significantly declines the specific extinction area by 44.12 m2·kg−1 compared to the coating without MMT by cone calorimeter. In addition, characterizations such as XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Notably, as the MQAS content increased, the corresponding MMT content decreased, and the remaining mass of SBR/FOSM increased, with SBR/FOSM‐4 reaching the highest. This condition occurred, because the introduction of MQAS enhanced the interface adhesion between FOSM and the rubber matrix, and the formed cross‐linked network structure is more stable, 7 thereby enhancing the thermal stability of the composite material 27 . The flake FOSM is evenly dispersed in the rubber matrix to form a more complicated propagation path, thereby strengthening the barrier of MMT to oxygen, free radicals, and heat in the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, as the MQAS content increased, the corresponding MMT content decreased, and the remaining mass of SBR/FOSM increased, with SBR/FOSM‐4 reaching the highest. This condition occurred, because the introduction of MQAS enhanced the interface adhesion between FOSM and the rubber matrix, and the formed cross‐linked network structure is more stable, 7 thereby enhancing the thermal stability of the composite material 27 . The flake FOSM is evenly dispersed in the rubber matrix to form a more complicated propagation path, thereby strengthening the barrier of MMT to oxygen, free radicals, and heat in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Although nanomaterials have a remarkable effect in reducing the peak heat release and mass loss rates, the SBR composites modified with nanomaterials are not satisfactory in traditional UL‐94 and LOI tests 3,6 . However, the nanosheet fillers have excellent smoke suppression and barrier properties and can be combined with other flame‐retardants in a polymer matrix to establish a synergistic flame‐retardant system 7 . Generally, clay nanofillers can promote the formation of the char layer in the condensed phase, thus preventing heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…MMT clay has been applied as an inorganic synergist to prepare the water-based intumescent flame retardant (IFR) ornamental coating for plywood. Analysis of heated products has revealed that residual nitrogenous polyaromatic structure and residual mass in the IFR coating were the results of the effect of MMT on the antioxidation properties of the char layer [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the constantly improving simulation modelling techniques for dimensioning and flame retardancy and smoke suppression attributes of Mg-Al LDH-based coatings for wood substrates. In the most recent publication by Hu et al [19] the synergistic action of MMT within water-based intumescent coating was proved to be effective in relation to fire resistance of plywood. All these studies demonstrate that bio-fillers and non-halogenated flame retardants could increase the thermal insulation of the protected substrates while decreasing the toxic potencies of gaseous products of combustion.…”
Section: Introductionmentioning
confidence: 99%